DESAIN SISTEM CETAK KARTU TANDA MAHASISWA UNIVERSITAS MERDEKA MALANG - Pamuntjar, Heris (Jurnal Teknologi dan Manajemen Informatika, 2015)
Student Identity Card ( KTM ) is valid evidence of membership of a student as an active student at a university. Therefore making the KTM should always use renewable integrated the data into a database system where the database contains related information on personal data of students, academic, and financial resources of the student . Thus the KTM function not only as a sign of an active student but pointed at the conclusion of financial transactions of students in each semester. To make the process of making the effectiveness KTM , at the Malang Merdeka University designing automation applications where these applications are connected to the central database that will check the completeness of all data and dependents of students before the students made ??a KTM. If all requirements are met, students stay in place and KTM photos can be directly printed on a special machine ID Card availableÂ DOI: https://doi.org/10.26905/jtmi.v1i1.611